Kebijakan Publik untuk Kesejahteraan Rakyat - Agus Suryono (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2014)
Welfare of the people is one of the goals of the state. In certain mechanism is required to make it happen that is reflected in public policy is made. Issues related to the problems that arise in realizing kesejahkteraan through public policy challenge. The right strategy in providing public policy that supports the well-being of the people in overcoming social problems are very important for further investigation.